IKKβ Is Essential for Adipocyte Survival and Adaptive Adipose Remodeling in Obesity - Park, Se-Hyung (Diabetes, 2016)
IκB kinase β (IKKβ), a central coordinator of inflammatory responses through activation of nuclear factor-κB (NF-κB), has been implicated as a critical molecular link between inflammation and metabolic disorders; however, the role of adipocyte IKKβ in obesity and related metabolic disorders remains elusive. Here we report an essential role of IKKβ in the regulation of adipose remodeling and adipocyte survival in diet-induced obesity. Targeted deletion of IKKβ in adipocytes does not affect body weight, food intake, and energy expenditure but results in an exaggerated diabetic phenotype when challenged with a high-fat diet (HFD). IKKβ-deficient mice have multiple histopathologies in visceral adipose tissue, including increased adipocyte death, amplified macrophage infiltration, and defective adaptive adipose remodeling. Deficiency of IKKβ also leads to increased adipose lipolysis, elevated plasma free fatty acid (FFA) levels, and impaired insulin signaling. Mechanistic studies demonstrated that IKKβ is a key adipocyte survival factor and that IKKβ protects murine and human adipocytes from HFD- or FFA-elicited cell death through NF-κB–dependent upregulation of antiapoptotic proteins and NF-κB–independent inactivation of proapoptotic BAD protein. Our findings establish IKKβ as critical for adipocyte survival and adaptive adipose remodeling in obesity.